2019
DOI: 10.1002/cne.24592
|View full text |Cite
|
Sign up to set email alerts
|

Long‐range projections from sparse populations of GABAergic neurons in murine subplate

Abstract: The murine subplate contains some of the earliest generated populations of neurons in the cerebral cortex, which play an important role in the maturation of cortical inhibition. Here we present multiple lines of evidence, that the subplate itself is only very sparsely populated with GABAergic neurons at postnatal day (P)8. We used three different transgenic mouse lines, each of which labels a subset of GABAergic, ganglionic eminence derived neurons. Dlx5/6‐eGFP labels the most neurons in cortex (on average 11%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 61 publications
(123 reference statements)
3
17
0
Order By: Relevance
“…Moreover, neonatal SP neurons were shown to project to the opposite hemisphere in other mammalian species (Chun et al, 1987; Antonini and Shatz, 1990). Our finding that Kcnab1 identifies a proportion of the ipsilaterally-projecting neurons in L6b/SP does not exclude the possibility that there are, although most likely minor, SP neurons that have contralateral projections that were not identified in this study due to experimental limitations such as tracer injections into a very restricted area compared with broad applications into the white matter or the corpus callosum in other studies (Ozaki and Wahlsten, 1998; Del Río et al, 2000; Hoerder-Suabedissen and Molnár, 2012; Boon et al, 2018). Hence, it would be most ideal if the tracing experiment is repeated with transgenic reporter line that would allow further characterization of the association neuron subclass, the axon trajectory that originates from this area, and their targets that may include other cortical regions.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Moreover, neonatal SP neurons were shown to project to the opposite hemisphere in other mammalian species (Chun et al, 1987; Antonini and Shatz, 1990). Our finding that Kcnab1 identifies a proportion of the ipsilaterally-projecting neurons in L6b/SP does not exclude the possibility that there are, although most likely minor, SP neurons that have contralateral projections that were not identified in this study due to experimental limitations such as tracer injections into a very restricted area compared with broad applications into the white matter or the corpus callosum in other studies (Ozaki and Wahlsten, 1998; Del Río et al, 2000; Hoerder-Suabedissen and Molnár, 2012; Boon et al, 2018). Hence, it would be most ideal if the tracing experiment is repeated with transgenic reporter line that would allow further characterization of the association neuron subclass, the axon trajectory that originates from this area, and their targets that may include other cortical regions.…”
Section: Discussionmentioning
confidence: 75%
“…Among 837 Kvβ1-positive neurons in L6b/SP, 92.7 ± 0.02% were CaMKIIα-positive (Figures 6E,F and Supplementary Table S2), suggesting that the majority of Kcnab1 -expressing neurons were excitatory. A recent study reported that no GABAergic neuron was detected among Ctgf -expressing neurons (Boon et al, 2018). As approximately 12% of Kcnab1 -expressing neurons were Ctgf -negative (Figure 6D and Supplementary Table S2), we examined single cell RNAseq data of cortical neurons (Tasic et al, 2016) to see if Kcnab1 is expressed in GABAergic neurons in L6b.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the excitatory versus inhibitory proportions of WMICs in the lar gibbon appears to be what would be expected for a neuronal population affiliated with the cerebral cortex. A recent study (Boon et al, in press) suggests that the mouse subplate is very sparsely populated with GABAergic neurons during development. It will be important to conduct similar studies in primates, potentially using some of the markers that are shared between these species (Wang et al, , ).…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether Drd1+ neurons are also Ctgf+, we immunostained Ai9 3 Drd1a-Cre brain slices with an anti-Ctgf antibody and found that about one-third of Drd1 neurons were immunoreactive to Ctgf (33.0% ± 2.2%, n = 1,001 neurons; Figure S1B). Both Drd1 and Ctgf neurons are excitatory because they were not immunoreactive to GAD67 ( Figure S1C; Boon et al, 2019). Morphological analysis revealed that Drd1 neurons were both pyramidal (i.e., they have a single pia-projecting apical dendrite) and non-pyramidal (n = 472 Drd1 neurons; Figure S1D); Ctgf neurons, on the other hand, were almost exclusively non-pyramidal (n = 330 Ctgf neurons; Figure S1D).…”
Section: Anatomical Monosynaptic Connections To L6bmentioning
confidence: 99%